(3cJGH Gdge hGdMRfs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CNHQJfG GdTjNI GdUGdMI GdeSfOg Ce GdaVd cQjeg heG RGd jHci MJi PgH HUQg bGd GdMSf hGddg Ef cGf Ydi GdCQV jheFP CcQe Ydi Gddg ef jYbhH s
(3BNQgG (B:s
(3ef QShd Gddg Udi Gddg Ydjg hSde HQLd SGLOkG jHci abGd GdMeO ddg GdPi CHcG CYjf GdeMRhfjf SLOkG Ydi hLhgge BNQ cJGH Gdge hGdMRf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdfSNI HgG MhGTs
(3HBNQgG SeGYGJ hbQGAGi cKjQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs